Evaluation through literature data on standardized ileal digestibility and basal ileal endogenous loss of amino acids associated with barley in pigs. (13th June 2014) - Spindler, H. K.; Mosenthin, R.; Eklund, M.
<x content-type="archive" xml:space="preserve">Abstract</x> This meta-analysis aimed to estimate the standardized ileal digestibility (SID) and the basal ileal endogenous amino acid losses (IAAend) in barley for growing pigs. In total, 38 different barley treatments published in 26 peer-reviewed papers were used for the meta-analysis containing information on dietary composition including amino acid (AA) contents of the assay diets, and (or) barley samples, as well as apparent ileal digestibility (AID) of AA in barley. The SID of AA was determined by either correcting AID of AA for their IAAend or by regression analysis between the apparent ileal digestible and total dietary AA contents. The SID values obtained by correcting the AID values for their IAAend amounted to 70%, 77%, 74% and 63% for Lys, Met, Thr and Trp, whereas those based on regression analysis method were 82%, 82%, 69% and 55%, respectively. Estimates of basal ileal endogenous loss of CP in ileal digesta varied considerably and averaged 11.84 g/kg dry matter intake (DMI), whereas IAAend for indispensable AA ranged from 0.05 g/kg DMI for Trp to 1.90 g/kg DMI for Leu. In most cases, these estimates were considerably higher than previously reported values for IAAend. The results of the present regression analysis indicate for most AA higher SID values compared with SID of most AA that were obtained by correcting AID values for IAAend. In view of the observed high variations in IAAend and the low CP content of the barley samples, estimating SID of AA based on literature data by means of the regression method may improve accuracy of SID coefficients for barley. In contrast, transformation of AID values into their corresponding SID values by using a constant correction factor for IAAend adds an additional source of error, thereby reducing the precision in estimating SID of AA.